Effect of Biofertilizer on the Productivity of Terraced Upland Rice (Oryza Sativa L.) - Thorie, Mhalevilie; Sarkar, N. C.; Kharutso, Atou (International Journal of Bio-resource and Stress Management, 2013)
An experiment was conducted in the experimental farm at School of Agricultural Sciences and Rural Development, Medziphema, Nagaland to observe the effect of different organic sources of nutrients on growth, yield and yield contributing characters of rice. The experiment was laid out in RBD replicated thrice with seven treatments i.e. Forest litter @ 20 t ha-1, Farmyard manure (FYM) @ 12 t ha-1, Poultry manure @ 4 t ha-1, FYM @ 12 t ha-1+Azotobacter @ 20 g kg-1 seed, Forest Litter @ 20 t ha1+Azotobacter @ 20 g kg-1 seed, Poultry manure @ 4 t ha-1+Azotobacter @ 20 g kg-1 seed and control. The plant dry weight was recorded to be highest in FYM @ 12 t ha-1+Azotobacter @ 20 g kg-1 seed followed by Poultry manure @ 4 t ha-1+Azotobacter @ 20 g kg-1 seed. FYM @ 12 t ha-1+Azotobacter @ 20 g kg-1 seed treated plot also produced highest yield contributing characters like number of panicles m-2, grain yield, straw yield, grains panicle-1, fertility percentage and test weight. Further there was an increase available NPK status of the soil in plots treated with organic manures.